2014
DOI: 10.1016/j.matchemphys.2014.05.032
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of sub-5 nm Co-doped SnO2 nanoparticles and their structural, microstructural, optical and photocatalytic properties

Abstract: A swift chemical route to synthesize Co-doped SnO 2 nanopowders is described. Pure andcrystalline nanoparticles were synthesized, with mean grain sizes < 5 nm and the dopant element homogeneously distributed in substitutional sites of the SnO 2 matrix. The UV-visible diffuse reflectance spectra of the Sn 1-x Co x O 2- samples reveal red shifts, the optical bandgap energies decreasing with increasing Co concentration. The samples' Urbach energies were calculated and correlated with their bandgap energies. The … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(22 citation statements)
references
References 49 publications
2
20
0
Order By: Relevance
“…The redshift of band gap in doped samples can be attributed to the sp-d exchange interactions between the band electrons and the localized d electrons of the Co 2? ions substituting Sn 4? ions [8,28,29]. Fang et al [30] in their work reported that redshift in the band gap of Fe 3?…”
Section: Characterization and Measurementsmentioning
confidence: 97%
See 2 more Smart Citations
“…The redshift of band gap in doped samples can be attributed to the sp-d exchange interactions between the band electrons and the localized d electrons of the Co 2? ions substituting Sn 4? ions [8,28,29]. Fang et al [30] in their work reported that redshift in the band gap of Fe 3?…”
Section: Characterization and Measurementsmentioning
confidence: 97%
“…(r = 0.75 Å ) is larger than that of Sn 4? (r = 0.69 Å ) [8,25]. Figure 2a provides the TEM image of sample CT3 and the particle size distribution with log-normal profile and selected area diffraction (SAED) patterns in its inset, and Fig.…”
Section: Characterization and Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The crystal structure type of SnO 2 is similar to the rutile phase structure of TiO 2 (dimensions of the unit cell: a = b = 0.47374 nm and c = 0.31864 nm, polar crystal with octahedral and space group no. 136 P42/mnm In one unit cell, the tin(IV) ion is surrounded by 6 oxygen ions and every oxygen is bordered by 3 tin(IV) ions, resulting in a coordination structure [8][9][10] as shown in Figure 1. The discovery of the photocatalytic properties of TiO 2 also led to a range of proposals for photocatalytic applications of related oxides.…”
Section: Literature Survey a Structure And Properties Of Snomentioning
confidence: 99%
“…As a result, the recombination of photo-induced electron-hole pairs is e®ectively inhibited, and the photocatalytic e±ciency is promoted by doping related trapped states. [35][36][37][38] Besides, the nonmetal doping is also an e®ective modi¯cation strategy for the improvement of visible-light-driven photocatalytic activity due to the bandgap narrowing. 34,[39][40][41] In particular, nonmetal doping such as N, C and S could make catalyst have better solar absorption and photocatalytic activity due to certain disadvantages of metal doping such as low thermal stability and enhanced recombination of charge carriers.…”
Section: Introductionmentioning
confidence: 99%